Maintenance programme at Menara Tabung Haji Kota Bharu / Nur Ain Farhana Nor Wadi - Nur Ain Farhana, Nor Wadi (2018)
This report is about the maintenance management of Menara Tabung Haji Kota Bharu that is located at the Kelantan. It is including the process of maintaining and operating in TH building which is maintained for internally. In this report it has put all the information that has been collected at Menara Tabung Haji Kota Bharu, Kelantan. Menara Tabung Haji is located at Kota Bharu, Kelantan. This building is an office building that at completed in year 1884. This building has 11 level of floor and one basements. This Menara Tabung Haji has the gross total area of site 66,351m2. This building completed with the broadband facilities increase their infrastructure and attract more company rent at this building. This building has the basement that used as parking area and many of office lots inside the building. This building was maintained by Tabung Haji Universal Builders (THUB) and their office located at the 3rd floor at Menara Tabung Haji. In my case study that has many type of the maintenance management that I have learn and put inside this report. Besides there is also has the maintenance programme and maintenance schedule reported in this report.